Evaluating the short-term effects of dance on motor and non-motor outcomes in people living with Parkinson’s: A crossover study - Anna M. Carapellotti; Matthew Rodger; Michail Doumas (PLoS ONE, 2025)
Purpose To investigate the short-term effects of a single dance class on motor and non-motor outcomes in people living with Parkinson’s. Methods A crossover design was used. Nineteen people participated. All participants took part in both dance and lecture control conditions seven days apart in a counterbalanced order. Outcomes of gait, balance, functional mobility, and aspects of cognition were measured before and after each condition. A visual analogue scale evaluated self-perceived changes in fatigue, energy, depression, anxiety, concentration, and movement. Statistical analyses were performed using 2x2 repeated-measures ANOVAs with time (pre vs. post) and condition (dance vs. lecture) as factors. Results Results showed functional mobility (measured by the Timed Up and Go) improved to a greater extent after dance compared to the lecture. Significant improvements after both dance and lecture sessions were demonstrated for other outcomes measuring balance, cognition, and anxiety, indicating either both conditions had a comparable impact or practice effects may have influenced results. Conclusions Further research is needed to confirm the presence and strength of the short-term effect of dance on functional mobility, to assess the impact of dancing on aspects of cognition and anxiety, and to hone the approach to studying the short-term effects of dance.